Gated electric field control on multi-layered structures with perpendicular magnetic anisotropy - Tan, Funan (Nanyang Technological University, 2019)
The ability to control the properties of ferro-metallic materials after device fabrication is a highly desirable feature for fundamental studies and technological advancements. In semiconductor-based devices, electric field control using a gate voltage to vary the conductivity is well established in commercialized devices. In comparison, the electric field control of spintronic devices is still in its infancy and there is a great deal of research interest surrounding this phenomenon. This thesis presents a comprehensive study and experimental implementation of electric field control on ferro-metallic based spintronic device. Despite the electric field screening effect of metals, electric field control was realized on a multilayer ferro-metallic structure. This modulation of anisotropy energy with electric field broadens the application of electric field control to include thicker multi-layered magnetic films. This allows spintronic devices to have a larger magnetic volume, thereby enhancing the thermal stability of the device. Another investigation on electric field control focuses on the dynamics of the magneto-ionic effect using a polymer as the insulating layer. The results show that thinner polymer layers lead to a faster magneto-ionic effect. This allows the possibility of flexible spintronics devices with high fabrication throughput. In addition, electric field control was employed to assist in the injection of domain walls in a geometrically constrained Hall cross structure. The reduction in the required current density for domain wall injection illustrates the wide range of application for electric field control on spintronic devices. Such applications also include novel techniques proposed in this thesis which manipulates domain walls using electric field control. The proposed technique propagates domain walls deterministically at high velocities without relying on any intrinsic or permanent extrinsic pinning features.